KEMAMPUAN BAHASA ANAK USIA 5-6 TAHUN MELALUI PERMAINAN KATA ORAK-ARIK - Veryawan, Veryawan; Jellysha, Jellysha (A?f?luna: Journal of Islamic Early Childhood Education, 2020)
This study aims to improve 5-6-year-children?s language skills through scrambled wordplay in TK Methodist Binjai. This research was conducted because there were problems with the lack of children's language skills in recognizing letters and words. This research was a classroom action research. The subjects in this study were 15 children of B-1 TK Methodist Binjai consisting of 4 boys and 11 girls. The object in this study was the language ability to recognize letters through scrambled wordplay. Data collection techniques were carried out through observation by filling in the observation table of the observed activities. This research was conducted in 2 (two) cycles. The results showed that the activity of playing scrambled words can improve children's language skills in recognizing letters and words. The results of observation in the first cycle obtained 46% of children who developed according to expectations and in the second cycle increased to 67% of children who developed as expected followed by 33% of children who developed very well. This showed that the activity of playing scrambled words to improve children's language skills in recognizing letters and words have been successful.